Depressive Symptoms and Functional Capacity in Elderly Institutionalized - Joyce Kelly Soares da Silva Soares Joyce (Universidad de Alicante, 2015)
This study aimed to evaluate depression and its relationship with functional capacity in the elderly living in long-stay institutions for the Elderly (ILPIs) of Maceió / AL. This was a correlative and comparative study among the participants, which consider the variables: criterion (depression) and background (functional capacity and indicators). 103 seniors attended eight ILPIs, 48 (46.6%) men and 55 (53.4%) women aged 60 up to 101 years (M = 76.2, SD = 10.1). Participants answered questions about: (1) Geriatric Depression Scale Yesavage, long version, (2) and Katz Index; (3) socio-demographic questionnaire. There were r Pearson correlation analysis and linear regression. It was found that 65% of the elderly had depressive symptoms and 56.4% had dependency related to functional capacity, with greater decline in women. It refers also that functional capacity was presented as a predictor of depressive symptoms and revealed a high incidence of these, in addition to functional disability in institutionalized elderly, pointing functional limitations as an indicator of depressive symptoms in these. We emphasize the importance of early detection of depression and the need for prevention of worsening of their symptoms.